2017
DOI: 10.1002/acn3.498
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo 11C‐PK PET study of microglia activation in Fatal Familial Insomnia

Abstract: ObjectivePostmortem studies reported significant microglia activation in association with neuronal apoptosis in Fatal Familial Insomnia (FFI), indicating a specific glial response, but negative evidence also exists. An in vivo study of local immune responses over FFI natural course may contribute to the understanding of the underlying pathogenesis.MethodsWe included eight presymptomatic subjects (mean ± SD age:44.13 ± 3.83 years) carrying the pathogenic D178N‐129met FFI mutation, one symptomatic patient (male,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…The six SYM‐carriers underwent an in‐depth neurological evaluation, including the ALS Functional Rating Scale‐Revised (ALSFRS‐r) for the assessment of severity of ALS and neuropsychological evaluation to evaluate cognitive efficiency. Ten healthy controls were included for statistical comparison (female/male 6/4; mean age 44.2 ± 10.5 years), previously recruited for different research studies 43,44,49 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The six SYM‐carriers underwent an in‐depth neurological evaluation, including the ALS Functional Rating Scale‐Revised (ALSFRS‐r) for the assessment of severity of ALS and neuropsychological evaluation to evaluate cognitive efficiency. Ten healthy controls were included for statistical comparison (female/male 6/4; mean age 44.2 ± 10.5 years), previously recruited for different research studies 43,44,49 …”
Section: Methodsmentioning
confidence: 99%
“…11 C‐PK11195 is the first, prototypical PET tracer for the in vivo detection of the 18‐kDa translocator protein (TSPO), an outer mitochondrial membrane protein which is overexpressed in activated microglia and reactive astrocytes, thus becoming a sensitive marker of neuroinflammation 35 . A TSPO overexpression as detected by 11 C‐PK11195 PET has been reported in several neurodegenerative disorders, such as Alzheimer’s disease and other neurodegenerative dementias, prion diseases, Parkinson’s disease, as well as in sALS 36–45 . In addition, 11 C‐PK11195 PET studies showed microglia activation also in preclinical stages of neurodegenerative conditions, 43,46,47 shedding light on the possible early molecular mechanisms of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation may increase the risk of inflammation and infection by altering immune function, whereas napping or extending sleep can restore immune system homeostasis [ 26 , 27 ]. Various studies have reported that microglia became activated in the brains of sleep-deprived mice, and the number and morphology of microglia were significantly positively correlated with neuronal apoptosis [ 28 , 29 ]. In this study, we found that NAR could effectively alleviate cell proliferation induced by LPS, suggesting that NAR may play a protective role by inhibiting microglia proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A single research group published two ( R )-[ 11 C]PK11195 reports that showed increased TSPO with varying patterns across subtypes of Creutzfeldt-Jakob disease [ 83 ] or Fatal Familial Insomnia [ 84 ]. There is no report using other radiotracers.…”
Section: Discussion On Each Group Of Diseasementioning
confidence: 99%